Role of endogenous retrovirus in control of feline leukemia virus infection and implications for cross species transmission - Chiu, Elliott S., author; VandeWoude, Sue, advisor; Hoover, Edward A., committee member; Ebel, Gregory D., committee member; Funk, W. Chris, committee member (Colorado State University. Libraries, 2019)
Endogenous retroviruses (ERV) are markers of ancient retroviral infections, though evolutionary forces have limited the capacity for ERV replication and virulence. While they are seldom considered infectious alone, they maintain the ability to interact with their exogenous retroviral (XRV) progenitors. In Chapter One, we review the interactions that exist between ERV and XRV dyads. One such couplet includes feline leukemia virus (FeLV), a common domestic cat pathogen. In Chapter Two, we review FeLV subgroup taxonomy and the methods used from which they were originally characterized. Though the domestic cat is regarded as the natural host for the virus, recent reports have documented FeLV infections in wild felids with pathogenic consequences. Chapter Three examines the root of a contemporary FeLV outbreak in Florida panthers (Puma concolor coryi), a species that lacks endogenous FeLV. Our phylogenetic analysis of the contemporary FeLV outbreak has further implicated domestic cats (Felis catus) as the origin of FeLV infections in wild felids. Furthermore, we detected a recombinant oncogenic variant in Florida panthers that is believed to be non-horizontally transmissible. These field studies have prompted us to examine the cellular basis of infection and intrinsic resistance to the virus. In Chapter Four, we interrogate the cellular basis of FeLV infections between puma (P. concolor) and domestic cat cells using in vitro approaches. We demonstrated that puma cells support greater infection and replication. Additionally, we documented enFeLV long terminal repeats (LTR) in domestic cats are negatively correlated to FeLV infection outcomes in vitro. Natural FeLV infections in both Florida panther and domestic cat tissues offered us the opportunity to examine end stage disease dynamics, which demonstrate that Florida panthers have the ability to produce more virus despite having lower proviral loads than domestic cats. The results of both in vivo and in vitro experiments prompted us to further investigate enFeLV-LTRs and their role in FeLV infection. Chapter Five took advantage of the publicly available data in the NCBI Sequence Read Archive (SRA) to evaluate enFeLV-LTR basal transcription levels. Data-mining the domestic cat transcriptome showed that lymphoid cells, which are relatively resistant to in vitro FeLV infection, transcribe more enFeLV elements than relatively susceptible cells (i.e., fibroblasts). We also identified microRNA transcripts are produced that have the potential ability to down-regulate FeLV RNA transcripts. In Chapter Six, we innovated a new methodology to characterize the enFeLV-LTR integration sites across the entire genome of 20 related and unrelated domestic cats in an attempt to uncover genes that may be influenced by LTR enhancement of gene expression. We found one LTR integration site in a limited number of cats that is within 1MB of APOBEC1, an antiviral gene, and that the most common gene found in close proximity to LTR integration sites are zinc fingers, a broad-acting class of regulatory proteins. Collectively, this groundwork provides future directions to uncover direct and indirect mechanisms of enFeLV-mediated restriction of FeLV infection. We conclude that because wild felids lack enFeLV, they may be more vulnerable to FeLV infection. As urbanization forces niche overlap and contact between wild and domestic felids, the risk of infection of these species is likely to increase, and thus it will be important to consider contacts between FeLV-infected domestic cats and wild felid populations during development of conservation action plans.
Keywords: feline leukemia virus; LTR integration; viral restriction; long terminal repeat; endogenous retrovirus; Puma concolor